1996
DOI: 10.1038/ng0496-410
|View full text |Cite
|
Sign up to set email alerts
|

A microdeletion in cytochrome c oxidase (COX) subunit III associated with COX deficiency and recurrent myoglobinuria

Abstract: We have identified a 15-bp microdeletion in a highly conserved region of the mitochondrially encoded gene for cytochrome c oxidase (COX) subunit III in a patient with severe isolated COX deficiency and recurrent myoglobinuria. The mutant mitochondrial DNA (mtDNA) comprised 92% of the mtDNA in muscle and 0.7% in leukocytes. Immunoblots and immunocytochemistry suggested a lack of assembly or instability of the complex. Microdissected muscle fibres revealed significantly higher portions of mutant mtDNA in COX-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(96 citation statements)
references
References 47 publications
3
91
0
2
Order By: Relevance
“…These results were consistent with the level of mutation found in the patient's leukocytes (1%; Ref. 16). …”
Section: Creation and Characterization Of Transmitochondrial Cellsupporting
confidence: 81%
See 3 more Smart Citations
“…These results were consistent with the level of mutation found in the patient's leukocytes (1%; Ref. 16). …”
Section: Creation and Characterization Of Transmitochondrial Cellsupporting
confidence: 81%
“…Since the patient's skeletal muscle harbored high levels of mutated mtDNA (92%; Ref. 16), these results suggested that the COX III mutation was absent or present at very low levels in muscle satellite cells (undifferentiated muscle precursor cells), in contrast to the skeletal muscle. Alternatively, it is possible that satellite cells and myoblasts containing high levels of mutation were selected against during culture because of a growth disadvantage.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This clinical variability is probably due to the number of nuclear genes involved in the expression, maturation, and assembly of the 13 COX subunits (Taanman 1997). So far, COX deficiency has been ascribed to mutations of either mtDNA-encoded COX subunits (Keightley et al 1996;Comi et al 1998;Hanna et al 1998;Bruno et al 1999;Clark et al 1999;Rahman et al 1999;Hoffbuhr et al 2000) or nuclear genes involved in assembly of functional complexes-namely, SURF1, SCO2, and COX10. Indeed, mutations in the nuclear SURF1 gene (MIM 185620 and MIM 256000) usually cause Leigh subacute necrotizing encephalomyopathy (Zhu et al 1998;Tiranti et al 1999;Poyau et al 2000) and have occasionally been associated with other clinical presentations (von Kleist-Retzow et al, in press).…”
Section: Introductionmentioning
confidence: 99%